Safety risk management for low molecular weight process‐related impurities in monoclonal antibody therapeutics: Categorization, risk assessment, testing strategy, and process development with leveraging clearance potential. (6th January 2021) - Luo, Haibin; Li, Yuling; Robbins, David; Wang, Sheau‐Chiann; Xi, Guoling; Cox, Matthew; Nicholson, Simone M.; Wei, Chenghong; Pabst, Timothy M.; Wang, William K.
Abstract: Process‐related impurities (PRIs) derived from manufacturing process should be minimized in final drug product. ICH Q3A provides a regulatory road map for PRIs but excludes biologic drugs like monoclonal antibodies (mAbs) that contain biological PRIs (e.g. host cell proteins and DNA) and low molecular weight (LMW) PRIs (e.g., fermentation media components and downstream chemical reagents). Risks from the former PRIs are typically addressed by routine tests to meet regulatory expectations, while a similar routine‐testing strategy is unrealistic and unnecessary for LMW PRIs, and thus a risk‐assessment‐guided testing strategy is often utilized. In this report, we discuss a safety risk management strategy including categorization, risk assessment, testing strategy, and its integrations with other CMC development activities, as well as downstream clearance potentials. The clearance data from 28 mAbs successfully addressed safety concerns but did not fully reveal the process clearance potentials. Therefore, we carried out studies with 13 commonly seen LMW PRIs in a typical downstream process for mAbs. Generally, Protein A chromatography and cation exchange chromatography operating in bind‐and‐elute mode showed excellent clearances with greater than 1, 000‐ and 100‐fold clearance, respectively. The diafiltration step had better clearance (greater than 100‐fold) for the positively and neutrally charged LMW PRIs than for the negatively charged or hydrophobic PRIs. We propose that a typical mAb downstream process provides an overall clearance of 5, 000‐fold. Additionally, the determined sieving coefficients will facilitate diafiltration process development. This report helps establish effective safety risk management and downstream process design with robust clearance for LMW PRIs.